Relationship between secondary schools agriculture teachers' motivation and use of contextual teaching - Abdul Latir, Siti Shuhaidah; Hamzah, Ramlah; Mat Rashid, Abdullah (Institute of Education, International Islamic University Malaysia, 2013)
Extensive studies have shown that teachers who are motivated show frequent use of required teaching practice. However, little is known about motivation and use of contextual teaching among secondary schools teachers in Malaysia. This study measured the motivation and use of contextual teaching among agriculture teachers in secondary schools in Malaysia. In addition, relationship between motivation and use of contextual teaching was determined. Data were collected from 280 secondary schools agriculture teachers, who were chosen through random sampling. The dependent variable was use of contextual teaching and the independent variable was motivation towards contextual teaching. Descriptive statistics have shown that most of secondary schools agriculture teachers had moderate motivation towards contextual teaching and they are frequently using contextual teaching. Majority of secondary schools agriculture teachers agreed that they use contextual teaching because they feel happy to overcome their students’ problems. Meanwhile data show that use of contextual teaching is at high level. More than half of respondents stated that they are open and empathetic towards students. Pearson Correlation shows that there is a significant relationship between secondary schools agriculture teachers’ motivation. In conclusion, secondary schools agriculture teachers’ motivation encourages them to use of contextual teaching frequently. Contextual teaching approach is suitable because it encourage students to participate actively in classroom. Moreover, contextual teaching allows equal opportunities for transfer of learning and satisfies various students’ needs. Recommendations for secondary schools agriculture teachers and areas for further studies are discussed.